Analysis-oriented stress–strain model for FRP-confined concrete with preload. (15th April 2017) - Pan, Yi; Guo, Rui; Li, Hongyi; Tang, Hongyuan; Huang, Jingxiang
Abstract: This paper is concerned with establishing an analysis-oriented stress–strain model for FRP-confined concrete in circular-section or square-section with preload. The paper provided the detail of the experimental results of 42 concrete columns confined with carbon fiber reinforced polymer (CFRP) with different preload ratios, then, based on the test results, this paper proposed a new failure surface theory about FRP-confined concrete considering the effect of preload. With the help of this new proposed failure surface theory and the widely accepted incremental process for actively-confined concrete which was used by most previous analysis-oriented models, a new analysis-oriented model was established. Compared with the test data, the proposed model provided a good correlation to the actual behavior. In addition, this paper also conducted the finite element simulation to verify the accuracy of this model.